Mobile-Based Dental Clinic Electronic Medical Record System - Tri Mukti Lestari; Abd Halim; Muhammad Atnang (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Medical records are essential documents in managing a person's health care and are used by various medical professionals to plan, provide, and evaluate patient care. According to the medical professional code of ethics, regulations keep medical records confidential. Dentists are required to make medical records for patients after carrying out an examination. So what about patients who want to know what treatments have been carried out during the treatment and care period? The patient will be given a medical record summary to find out this. This research aims to build a resume of medical records for patients without violating the ethical code of the medical profession. Use the Rapid Application Development (RAD) method to make this system. The results show that the system successfully displays a summary of patient's medical records, per the Dental Medical Record Guidelines [1]. It is hoped that with a mobile-based electronic medical record system, patients will be more diligent and more concerned about having their dental health checked at least once every six months. Keywords—Electronic medical records, Dentistry, Mobile based